VARIABILITAS GENETIK GENERASI F2 PADA KARAKTER UKURAN BIJI KEDELAI [Glycine Max (L.)] - Ratna Fitri Yenny (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2010)
ABSTRACTSeed size characters measure represent an important factor of production and determinant in physical indicator to determine consumer fascination as completely seed. Genetic Variability represent the breeder seeds basis to find a new variety that genetically having high yield. This research aim to to know seed size measure character genetic variability from F2 soybean, crossing between big seed size measure parental with small seed size measure parental. Result of the research showed that there are wide of genetic variability. Genetic variability of vascular bundle system is an important new varieties parameter in recombining genetically high yield. A hundred seed weight, seed length, seed thickness and seed width had wide genetic and phenotypic variabilityKey words: genetic variability, seed size, F2, soybean